(untitled) (Bangladesh Journal of Botany, 2018)
The present study used two varieties (BRRI dhan29 and Hybrid dhan Taj1) of rice and (control) and six different concentrations of soil enhancer XXL [125% (1.88/1.5 g/l), 100% (1.5/1.5 g/l), 75% (1.125/1.5 g/l), 50% (0.75/1.5 g/l), 33% (0.50/1.5 g/l) and 25% (0.38/1.5 g/l)] with recommended doses of (N, P, K, S and Zn) fertilizers. Significant variation was observed in different yield contributing characters with soil enhancer (XXL) application. Among the different soil enhancer (XXL) concentrations, 75% XXL provided the highest yield (10.58 t/ha). With 75% XXL, BRRI dhan29 and Hybrid dhan Taj1 provided their highest grain yield (11.09 t/ha and 10.07 t/ha, respectively). However, BRRI dhan29 performed well due to yield attributes (fertile tillers/hill, panicle length and shoot dry matter/hill which were 11.94, 23.95 cm and 21.59 g, respectively) than that of Hybrid dhan Taj1 with 75% XXL applied.